Carcinoid Heart Disease Associated with Primary Ovarian Carcinoid Tumor: A Rare Presentation - Rawaha Ahmad; Ian Loke; Fizza Saifullah; Hafsa Zafar; Saddam Hussain Abbasi (Heart Views)
Primary ovarian carcinoid tumors, an extremely rare subset of ovarian malignancies (<0.1% of cases), typically manifest with abdominal pain and bloating. The occurrence of carcinoid heart disease (CHD) without classic carcinoid syndrome features is exceptionally uncommon. We report a 54-year-old female presenting with dyspnea and edema over months, lacking typical carcinoid syndrome signs. Initial assessments diagnosed heart failure, supported by elevated NT-Pro BNP, echocardiographic right ventricular dilation, and pulmonary/tricuspid valve regurgitation (normal left ventricular function). Right heart catheterization showed normal pulmonary/right ventricular pressures. Subsequent investigations (computed tomography thorax abdomen pelvis, 5-hydroxyindole acetic acid levels) strongly suggested carcinoid disease, confirmed by an octreotide scan revealing an octreotide-secreting ovarian carcinoid tumor. Surgical intervention included tricuspid and pulmonary valve repair, total abdominal hysterectomy, and bilateral salpingo-oophorectomy. Primary ovarian carcinoid tumors, though rare, may lead to unexpected complications like CHD. Timely diagnosis and intervention are pivotal for optimizing patient outcomes in such cases.